The use of pulsed high-speed liquid jet for putting out gas blow-out - Semko, A; Rusanova, O; Kazak, O; Beskrovnaya, M; Vinogradov, S; Gricina, I (The International Journal of Multiphysics, 2015)
The experimental analysis of putting out a gas blow-out with the help of pulse liquid flow with high velocity, which generates by powder pulse water-cannon are carried out. The flow velocity resides in range from 300 to 600 m/s in experiments depends on charge energy. Velocity of the flow head right near the gas flame determined with the help of laser contactless measuring instrument of velocity. Photography of flow was carried out. According to the preliminary test results the hydrodynamic parameters of powder pulse water-cannon for obtaining liquid flow with depend velocity are calculated. It is shown, that around the liquid flow of high velocity in air produced fine water spray with high velocity in large cross section area that effective knock down the gas blow-out at the distance 5-20 m from installation.